2012
DOI: 10.1587/elex.9.1855
|View full text |Cite
|
Sign up to set email alerts
|

Miniature monopole fractal antenna with inscribed arrowhead cuts for UWB applications

Abstract: Abstract:The letter presents the results of a novel miniature fractal monopole antenna that exhibits ultra wideband (UWB) performance. The unique fractal patch generates multiple resonances that results in significant improvement in the antenna's impedance bandwidth of 152%. The antenna essentially radiates omni-directionally and its measured performance exceeds the UWB specifications defined by the Federal Communications Commission (FCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…There are other prototypes with slightly better characteristics such as gains and bandwidths, but they use fractal techniques [23][24][25][26]. However, the dimensions are increased considerably compared to the one presented by Afifi et al (10 × 10 mm 2 ) [20], and the performance of this UWB antenna is dependent on the fractal patch, feeding, slots on the partial ground plane achieving approximately gains of 4 dB, and omnidirectional radiation patterns.…”
Section: Uwb Antennas In Microwave Imaging Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are other prototypes with slightly better characteristics such as gains and bandwidths, but they use fractal techniques [23][24][25][26]. However, the dimensions are increased considerably compared to the one presented by Afifi et al (10 × 10 mm 2 ) [20], and the performance of this UWB antenna is dependent on the fractal patch, feeding, slots on the partial ground plane achieving approximately gains of 4 dB, and omnidirectional radiation patterns.…”
Section: Uwb Antennas In Microwave Imaging Systemsmentioning
confidence: 99%
“…One of the main challenges in the design of these antennas is related to the physical size in order to allow a greater number of antennas to collect more information of the scattered signal for a successful image reconstruction, as well as to achieve a wider bandwidth to get a high-resolution image [20] and reduce the distortion in transmission of short-duration pulses [21]. Several antennas were proposed for cancer detection as monopole antennas [14,22], fractal antennas [23][24][25][26], antipodal Vivaldi antennas [27], slot antenna [28,29], and patch antenna [30], as will be described below.…”
Section: Radiofrequency As a Cancer Diagnostic Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, there has been an expanding quantity of literature on fractal UWB antennas depending on self‐similarity and space filling property that contain many advantages such as multiband, broadband, and UWB properties, miniaturization of antenna dimension. In , a square shape fractal antenna of electrical dimension 0.47 λ × 0.47 λ at 2.355 GHz low frequency is proposed for wireless communications, medical imaging, and UWB applications.…”
Section: Introductionmentioning
confidence: 99%
“…Wireless local area network (WLAN) and worldwide interoperability for microwave access (WiMAX) have been widely applied in mobile devices, such as handheld computers and intelligent phones [2]. Also many efforts in UWB antenna fields have been reported that more descriptions come in [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%